The time course of moral decision making in bilinguals' native and foreign language - Brouwer, Susanne (Frontiers in Language Sciences, 2023)
Previous work has shown that moral decision making depends on whether moral dilemmas are presented in the native or a foreign language (Foreign Language effect; e.g., Costa et al., 2014).In that work, the focus was on bilinguals' final decision, but the tasks used, failed to capture the processes involved over time. The aim of this study was to examine the time course of moral decision making in bilinguals' native and foreign language prior to and after their moral decision. In a visual-world eye-tracking experiment, 82 Dutch-English bilinguals listened to 20 moral dilemmas (e.g., would you kill one to save five?) in their native or foreign language, while looking at two pictures containing key people involved in the dilemmas. These pictures illustrated (1) the person/people that is/are sacrificed, and (2) the person/people that is/are not sacrificed, depending on the participants' decision which was measured with yes/no-questions.The Foreign Language effect was replicated for the decisions on the personal dilemmas. Importantly, the eye gaze data showed that in the native language, listeners looked at the person who they did not sacrifice, whereas in the foreign language, they looked at the people who they sacrificed. A speculative explanation is that bilinguals might have experienced guilt in the native language, and therefore focused attention on the person they did not sacrifice, while in the foreign language they might have experienced less guilt because they focused attention on the people they sacrificed. More research is needed to understand the influence of factors such as emotion reduction and cognitive load on moral decision making.